1997
DOI: 10.1128/jvi.71.1.824-827.1997
|View full text |Cite
|
Sign up to set email alerts
|

Murine coronavirus packaging signal confers packaging to nonviral RNA

Abstract: Studies of defective interfering (DI) RNAs of the murine coronavirus mouse hepatitis virus (MHV) suggest that a 69-nucleotide-long packaging signal is necessary for MHV genomic RNA packaging into MHV particles. In this study we showed that when RNA transcripts that consisted of a non-MHV sequence and the packaging signal were expressed in MHV-infected cells, they were packaged into MHV particles. Those RNA transcripts that lacked the packaging signal or those containing a mutated packaging signal did not packa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…PSs of alpha-and gammacoronaviruses were first identified for TGEV and IBV (Escors et al, 2003;Penzes et al, 1994). MHV DI RNA studies revealed a 69-nt SL structure that was (i) located in the 3 0 region of ORF1b, (ii) confirmed to be required for DI RNA packaging, and (iii) shown to interact with the viral N protein (Fosmire et al, 1992;Molenkamp and Spaan, 1997;Woo et al, 1997). Subsequent studies indicated that a larger PS element and, possibly, additional factors are required for optimal packaging efficiency (Bos et al, 1997;Cologna and Hogue, 2000;Narayanan and Makino, 2001).…”
Section: Rna Elements Involved In Coronavirus Genome Packagingmentioning
confidence: 99%
“…PSs of alpha-and gammacoronaviruses were first identified for TGEV and IBV (Escors et al, 2003;Penzes et al, 1994). MHV DI RNA studies revealed a 69-nt SL structure that was (i) located in the 3 0 region of ORF1b, (ii) confirmed to be required for DI RNA packaging, and (iii) shown to interact with the viral N protein (Fosmire et al, 1992;Molenkamp and Spaan, 1997;Woo et al, 1997). Subsequent studies indicated that a larger PS element and, possibly, additional factors are required for optimal packaging efficiency (Bos et al, 1997;Cologna and Hogue, 2000;Narayanan and Makino, 2001).…”
Section: Rna Elements Involved In Coronavirus Genome Packagingmentioning
confidence: 99%
“…This interaction has so far been reported only for MHV, by Makino and co-workers. These workers had shown earlier that the 69-nucleotide packaging signal located in the pol1b gene could mediate the incorporation into virions of RNAs of even noncoronaviral origin (Woo et al, 1997). They subsequently showed that this incorporation is most likely effected by a direct and specific interaction of the signal with the M protein.…”
Section: Envelope-nucleocapsid Interactionsmentioning
confidence: 99%
“…The signal appeared to be sufficient for RNA packaging as its inclusion allowed a synthetic subgenomic mRNA of MHV-A59 to be packaged specifically; the encapsidation efficiency of the mRNA was, however, significantly lower than that of the defective genomic RNA from which it was transcribed . Even a nonviral RNA was found to be packaged into MHV particles when provided with the packaging signal (Woo et al, 1997). Buoyant density analysis of the particles revealed that the RNA was not assembled separately but copackaged with helper virus RNA.…”
Section: Packaging Signalsmentioning
confidence: 99%
“…Studies of the genomic PSs in CoVs have been mainly focused on group IIa CoVs in the past, e.g. MHV and BCoV (Fosmire et al, 1992;Makino et al, 1990;van der Most et al, 1991;Woo et al, 1997;Chen et al, 2007;Cologna and Hogue, 2000). For other groups of CoVs, e.g.…”
Section: Structure Probing Of the Sl5 Substructure In Hcov-229e And Smentioning
confidence: 99%